Development of an Antigen Delivery Platform Using Lactobacillus acidophilus Decorated With Heterologous Proteins: A Sheep in Wolf’s Clothing Story - Uriza, Paula J.; Trautman, Cynthia; Palomino, María M.; Fina Martin, Joaquina; Ruzal, Sandra M.; Roset, Mara S.; Briones, Gabriel (Frontiers in Microbiology, 2020)
S-layers are bacterial structures present on the surface of several Gram-positive and Gram-negative bacteria that play a role in bacterial protection. In Lactobacillus acidophilus (L. acidophilus ATCC 4356) the S-layer is mainly composed of the protein SlpA. A tandem of two copies of the protein domain SLP-A (pfam: 03217) was identified at the C-terminal of SlpA, being this double SLP-A protein domain (in short dSLP-A) necessary and sufficient for the association of the protein to the L. acidophilus cell wall. A variety of proteins fused to the dSLP-A domain were able to spontaneously associate with high affinity to the cell wall of L. acidophilus and Bacillus subtilis var. natto, in a process that we termed decoration. Binding of dSLP-A-containing-proteins to L. acidophilus was stable at conditions that mimic the gastrointestinal transit in terms of pH, proteases, and bile salts. To evaluate if protein decoration of L. acidophilus can be adapted to generate an oral vaccine platform, a chimeric antigen derived from the bacterial pathogen Shiga-toxin-producing Escherichia coli (STEC) was constructed by fusing the sequences encoding the polypeptides EspA36-192, Intimin653-953, Tir240-378, and H7 flagellin352-374 (EITH7) to the dSLP-A domain (EITH7-dSLP-A). Recombinantly expressed EITH7-dSLP-A protein was affinity purified and combined with L. acidophilus cultures to allow the association of the chimeric antigen to the bacterial surface. EITH7-decorated L. acidophilus was orally administered to BALB/c mice and the induction of anti-EITH7 specific antibodies in sera and feces determined by ELISA. Mice presenting significantly higher anti-EITH7 antibodies titers were able to control more efficiently an experimental STEC infection than mice that received the non-decorated L. acidophilus carrier, indicating that antigen-decorated L. acidophilus can be adapted as a mucosal immunization delivery platform to elicit a protective immune response for vaccine purposes.